2021
DOI: 10.1002/acn3.51344
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing‐related neural oscillation: an intracranial EEG study

Abstract: Objective: Swallowing is a unique movement due to the indispensable orchestration of voluntary and involuntary movements. The transition from voluntary to involuntary swallowing is executed within milliseconds. We hypothesized that the underlying neural mechanism of swallowing would be revealed by high-frequency cortical activities. Methods: Eight epileptic participants fitted with intracranial electrodes over the orofacial cortex were asked to swallow a water bolus and cortical oscillatory changes, including … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The cortex may trigger swallowing and modulate the brainstem (Ertekin and Aydogdu, 2003), and HG activities appeared in the cortex during the voluntary swallowing phase rather than during the involuntary swallowing phase (Hashimoto et al, 2021b). These findings support that the cooperation between voluntary and involuntary movements and the cortex and the brainstem is necessary for normal swallowing.…”
Section: Profiles Of Motor-and Sensory-related Pacsupporting
confidence: 54%
See 4 more Smart Citations
“…The cortex may trigger swallowing and modulate the brainstem (Ertekin and Aydogdu, 2003), and HG activities appeared in the cortex during the voluntary swallowing phase rather than during the involuntary swallowing phase (Hashimoto et al, 2021b). These findings support that the cooperation between voluntary and involuntary movements and the cortex and the brainstem is necessary for normal swallowing.…”
Section: Profiles Of Motor-and Sensory-related Pacsupporting
confidence: 54%
“…Therefore, swallowing is divided into two components: voluntary and involuntary movement (Jean, 2001). Our iEEG study showed that HG activities in the cortex along the Sylvian fissure achieved the maximum values at the transition time from the voluntary to the involuntary phase (Hashimoto et al, 2021b). Moreover, swallowing is a unique movement since cooperation between motor output and sensory input is involved.…”
Section: Ll Open Accessmentioning
confidence: 79%
See 3 more Smart Citations